Phospho-Signaling at Oocyte Maturation and Fertilization: Set Up for Embryogenesis and Beyond Part I. Protein Kinases - Hasan, A.K.M. Mahbub; Matsumoto, Takashi; Kihira, Shigeru; Yoshida, Junpei; Sato, Ken-ichi (IntechOpen, 2012)
None